REFORMULASI NORMA HAK DAN KEWAJIBAN SUAMI ISTRI DALAM HUKUM KELUARGA DI INDONESIA (Sebuah Upaya Pengarusutamaan Gender dalam Pembaharuan Undang-undang Nomor 1 Tahun 1974 Tentang Perkawinan) - Muhammad Busyrol Fuad (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Fulfillment of the Rights and Duties of husband and wife is an important factor for the creation of a family who sakînah, mawaddah, wa rahmah. In creating an ideal relationship of husband and wife, both of them must have a role and equal opportunity in the public domain or domestic. This is not reflected in the Law No. 1 of 1974 About Marriage, for example, the husband bears responsibility as breadwinner and protector for his wife. Instead wife are given responsibilities as housewives to manage domestic. The research aims to determine the norms of the rights and duties of husband and wife in Act No. 1 of 1974 About Marriage are gender refraction. This type of research used in this research is normative, using the approach of legislation and historical approaches. Based on the analysis of the data that has been collected, it is concluded that some of the provisions concerning the rights and duties of husband and wife in the Law of Marriage Act is gender refrection. Among them, the husband is the head of the household and the wife is a housewife (Article 31, paragraph 3), the husband is obliged to provide for his wife and protect the family in accordance with his ability (34, paragraph 1), while the wife is the household as much as you (article 34 paragraph 2). According to the authors conclusion, that Article 31, paragraph 3 shall be deleted because it is gender refraction, and the existence of another article which is a translation of this article deserves to be renewed.Kata Kunci : Gender Mainstreaming, Rights and Duties of Husband and Wife, Marriage Law